Preparation of model Rh-CeO2 catalysts by pulsed laser ablation in liquid - Kibis, Lidiya S.; Krotova, A. I.; Fedorova, Elizaveta A.; Kardash, Tatyana Yu; Stonkus, Olga A.; Svetlichnyi, Valerii A.; Slavinskaya, Elena M.; Boronin, Andrei I. (Journal of structural chemistry)
The powders of Rh and CeO2 are synthesized by pulsed laser ablation in liquid. The Rh-CeO2 model catalysts are prepared by the calcination of these powders in a wide temperature range from 450 degrees C to 1000 degrees C. The formation of individual and mixed (rhodium-and cerium-containing) phases with increasing temperature of catalyst calcination is studied by powder XRD and Raman spectroscopy. The redox properties of prepared catalysts are tested in a temperature-programmed reaction of CO reduction; their catalytic properties are studied on the example of CO oxidation. It is shown that the catalysts remain stable during catalytic tests due to the formation of a nano-heterophase system consisting of rhodium oxide (Rh2O3) and cerium oxide (CeO2) nanoparticles. The discovered high stability is most likely explained by the formation of the Rh3+-CeO2 species with the localization of Rh3+ ions in subsurface CeO2 layers due to the contacts between rhodium oxide and cerium oxide nanoparticles. Introducing Rh3+ ions into Ce4+ positions of the CeO2 lattice distorts the cerium oxide structure and leads to the formation of active oxygen species interacting with CO at low temperatures. The catalysts are shown to preserve high activity in the reaction of low-temperature CO oxidation even after the calcination at 1000 degrees C.